The role of affective commitment in promoting knowledge sharing in Zimbabwean higher education - Audrey Dumbura; Serife Eyupoglu (South African Journal of Business Management)
Purpose: This study explores the effect of affective commitment on knowledge-sharing behaviour (KSB), highlighting the role of positive and negative affect (emotions) in shaping this relationship in higher educational institutions. A robust knowledge-sharing environment fosters decent work encouraging institutional members to collaborate and share knowledge for mutual success.